Peningkatan Kreatifitas Guru Dalam Pembuatan Learning Management System (LMS) Berbasis Moodle - Astriani, Linda; Wicaksono, Dirgantara; Sahrul, Muhammad; Rahmadani, Salsa Alvianita (Edumedia Solution, 2023)
Due to the effects of COVID-19 on the educational landscape, teachers and students are competing with one another to use online learning. The goal of this volunteer work is to educate 13 teachers at Harapan Ibu Pondok Pinang Islamic Middle School on how to boost teacher creativity using a Moodle-based LMS. Preliminary research, outreach, training, and assessment are the strategies employed. The teachers were able to learn more creatively thanks to the LMS as a result. This practice supports educators' ongoing efforts to develop inventive and imaginative instructional resources. With the help of this training, teachers should be able to use Moodle-based LMS to improve their teaching inventiveness and continue to mentor students both offline and online through Moodle-based LMS.